Barking pigs. - Ong, Bee Lee; Arshad, Siti Suri (Universiti Putra Malaysia Press, 2013)
A Problem-based Learning (PBL) approach to address investigation of a zoonotic disease, Nipah virus infection in pig and human. It emphasizes on the students knowledge on epidemiology, immunology, diagnostic out, biosafety, prevention and control and international compliant (OIE requirement) to certify disease freedom. It stresses on the importance of using One Health approach in involving multi-sectoral cooperation and collaboration in combating the disaster in Peninsular Malaysia 1998-1999.